TI_GERICHTE 80.2011.71 vom 15. April 2011 , Condono: condizioni, imposta sugli utili immobiliari non dovuta, decisione esecutiva - TI Tribunale d'appello (2011)
Condono: condizioni, imposta sugli utili immobiliari non dovuta, decisione esecutiva